Multivariate Analysis of Trace Element Contents in Angelica sinensis and Soil - Jin1, Hang; Wang1, Yuanzhong; Zhao1, Zhenling; Yang1, Weize; Yang1, Meiquan; Zhang1, Ji; Zhang1, Jinyu (Asian Journal of Chemistry, 2011)
The contents of Hg, Mn, As, Pb, Cu, Mg, Cd, Ni, Fe, Zn and Cr in Angelica sinensis (Oliv.) Deils of Yunnan and soil from 14 locations in Yunnan province of China were determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The results showed high contents of Zn, Cu, Pb, Fe and Mg in soil and Mg, Fe, Mn, Zn and Cu in A. sinensis compared with other trace elements. Among the determined 11 trace elements, A. sinensis had relatively strong enrichment to Mn, Cr and Mg. In A. sinensis, As-Mg and Ni-Fe were significantly positive correlated; while As-Ni, Cu-Cd, Pb-Fe were significantly negative correlated. Meanwhile, As(plant)-As(soil), Cd(plant)-Hg(soil), Cu(plant)-Mn(soil) and Ni(plant)-Pb(soil) showed strong positive correlation, whereas Mn(plant)-Cu(soil), Pb(plant)-Cd(soil) and Cr(plant)-Pb(soil) showed negative correlation. This paper presented the trace elements properties of A. sinensis and expected to be useful for quality evaluation of this medicinal plant.